Are social media good or bad for employees? It depends on when they use them. Issue 4 (12th March 2022) - Labban, Alice; Bizzi, Lorenzo
ABSTRACT: Organisations are currently adopting opposite stances when it comes to allowing employees to use social media at work, some entirely banning access to social media and others permitting their unconstrained use. A possible reason for these opposite approaches is that the outcomes of social media are still uncertain and research on the effects of social media on employee behaviours has produced opposite findings. We help solve controversy in empirical findings, showing that social media could be either beneficial or deleterious depending on the situations in which employees use them. Our empirical study shows that the use of social media before starting work makes employees experience positive emotions of happiness and attentiveness, which translate into beneficial work behaviours, such as networking with colleagues. However, when employees use social media while working, they experience negative emotions of fatigue and guilt, which make them engage in counterproductive work behaviours. The findings informs specific recommendations for social media policies, which are discussed at the end.